CRITERIA FOR SETTING TARIFFS IN COLLECTIVE MANAGEMENT OF COPYRIGHT - COMPETITION LAW PERSPECTIVE (EU and comparative law issues and challenges series (ECLIC), 2024)
The purpose of this research is to explore the criteria for setting tariffs in the collective management of copyright from a competition law perspective. The study aims to identify how competition law interacts with copyright-specific characteristics, including protecting authors’ rights and the operational particularities of collective management organisations (CMOs). By analysing European Union directives and case law from the Court of Justice of the European Union (CJEU), this paper investigates whether the tariffs imposed by CMOs, particularly those in dominant market positions, comply with competition rules. The research employs a legal analytical approach, reviewing key legal texts and case law to provide a comprehensive understanding of criteria used in tariff-setting and their regulation under both copyright and competition law. It evaluates whether tariffs reflect the economic value of the rights used, considering the nature and scope of use and the economic value of the services provided by CMOs. The major findings of this research highlight that CMOs, as de facto or de jure monopolies, must set tariffs based on fair and objective criteria to avoid abuses of dominant positions. The implications of these findings suggest that appropriate regulation of tariffs, aligned with competition law, ensures a balanced relationship between protecting authors’ rights and promoting fair competition in the marketplace. The discussion here contributes to the ongoing debate on the regulation of collective management and the role of competition law in safeguarding both authors’ interests and market fairness.